2010
DOI: 10.1111/j.1574-6941.2010.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community characterization and dynamics of indigo fermentation

Abstract: Indigo fermentation has been traditionally performed for dyeing textiles in Japan. Limited information is available on the microbiota involved and the succession of the bacterial community structure during indigo reduction. We investigated the bacterial community structure associated with indigo fermentation using denaturing gradient gel electrophoresis and clone library analyses of a PCR-amplified 16S rRNA gene in the early phase of fermentation carried out in our laboratory. A marked substitution of Halomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…In addition to these isolates, we have also recently isolated the indigo-reducing bacteria Alkalibacterium psychrotolerans, Alkalibacterium iburiense and Alkalibacterium indicireducens from indigo fermentation liquors obtained from Date City, Iburi, Hokkaido, Japan and Tokushima Prefecture, Shikoku, Japan (Nakajima et al, 2005;Yumoto et al, 2004Yumoto et al, , 2008. It has also been demonstrated that, other than the abovementioned species, several isolates of micro-organisms from indigo fermentation liquor were able to reduce indigo (Aino et al, 2010). Among the isolates, a novel indigo-reducing bacterium 'Oceanobacillus indicireducens' was recently described (Hirota et al, in press).…”
mentioning
confidence: 99%
“…In addition to these isolates, we have also recently isolated the indigo-reducing bacteria Alkalibacterium psychrotolerans, Alkalibacterium iburiense and Alkalibacterium indicireducens from indigo fermentation liquors obtained from Date City, Iburi, Hokkaido, Japan and Tokushima Prefecture, Shikoku, Japan (Nakajima et al, 2005;Yumoto et al, 2004Yumoto et al, , 2008. It has also been demonstrated that, other than the abovementioned species, several isolates of micro-organisms from indigo fermentation liquor were able to reduce indigo (Aino et al, 2010). Among the isolates, a novel indigo-reducing bacterium 'Oceanobacillus indicireducens' was recently described (Hirota et al, in press).…”
mentioning
confidence: 99%
“…Phenotypic and chemotaxonomic characterizations, phylogeny based on the 16S rRNA gene sequence, and DNA-DNA hybridization showed that the isolates were represented a novel species within a novel genus in the family Bacillaceae, for which the name Fermentibacillus polygoni gen. nov., sp. nov. is proposed.The isolation of a bacterial strain that can grow on a medium containing indigo fermentation fluid was attempted using a medium containing fermented indigo.Fermented indigo liquor was prepared in our laboratory (Aino et al, 2010). The fermented liquor contained Sukumo (composted leaves of the Japanese indigo plant), wood ash extract, wheat bran and a very small amount of Japanese rice wine, and was maintained at pH 11 and 30 C. An aliquot of the sample was inoculated onto an indigo fermentation liquor medium (IFLA agar medium) containing 100 ml indigo fermentation liquor prepared in our laboratory, 100 ml 10 % Na 2 CO 3 solution (sterilized separately and then mixed with the autoclaved medium at 10 % ratio) and 15 g agar in 1 l distilled water (pH 10).…”
mentioning
confidence: 99%
“…Fermented indigo liquor was prepared in our laboratory (Aino et al, 2010). The fermented liquor contained Sukumo (composted leaves of the Japanese indigo plant), wood ash extract, wheat bran and a very small amount of Japanese rice wine, and was maintained at pH 11 and 30 C. An aliquot of the sample was inoculated onto an indigo fermentation liquor medium (IFLA agar medium) containing 100 ml indigo fermentation liquor prepared in our laboratory, 100 ml 10 % Na 2 CO 3 solution (sterilized separately and then mixed with the autoclaved medium at 10 % ratio) and 15 g agar in 1 l distilled water (pH 10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Alkalibacterium indicireducens was isolated from indigo fermentation liquors obtained from Tokushima Prefecture, Shikoku, Japan (Yumoto et al, 2008). Aino et al (2010) demonstrated that several isolates other than the above-mentioned species of micro-organisms from indigo fermentation liquor can reduce indigo. On the basis of these findings, it is clear that indigo-reducing ability is present not only in the genus Alkalibacterium but also in other genera belonging to the phylum Firmicutes, including the genera Amphibacillus, Bacillus and Oceanobacillus.…”
mentioning
confidence: 99%